Women and Land Tenure in Zambia: Legal and Customary Challenges for Women - , Roy Kalinda; , Masauso Chirwa; , Kusanthan Thankian (Archives of Current Research International, 2022)
Zambia has a dual land tenure system recognized by the constitution and land policy which govern land in all parts of the Country. The Customary system governs the land under the control of traditional leaders while the statutory tenure system governs all land that is titled. In 2021, just before the general presidential and parliamentary elections, a new land policy was launched in Zambia with a 50% provision of land to all women. The new land policy aims at gender equality in land ownership in line with the Southern African Development Community (SADC) and African Union (AU) protocols. This policy has a gender component that deals specifically with the requirement of allocating land to women, the youth and disabled people. Even under statutory land, gender inequalities still remain minimally challenged same despite policy pronouncements which are rarely transformed into political actions intended to deal with gender inequalities in land ownership which is a serious problem among poor women in all the ten provinces. In all these provinces, women are the minority in terms of land ownership in both urban and rural communities. This situation is compounded by the high poverty levels and illiteracy among both urban and rural women. Provisions of gender equity measures in policies are important steps towards gender equality and should be encouraged all the time and policy reviews should equally take on board emerging issues from time to time. However, the current situation in the country of formulating policies with gender inclusive measures seems to be an end itself because policies are not accompanied by practical programmes aimed at dealing with gender inequalities in different locations and remote communities where the customary tenure system remains unchallenged. Government interventions through land policies have achieved some gains but more would have been achieved if deliberate programmes were instituted on land redistribution especially on statutory land to ensure that the disadvantaged groups even among women benefit from policy changes. Ratification of international conventions that are aimed at combating gender discrimination should be accompanied with practical programmes and policies which should be monitored and evaluated from time to time to ensure that practical progress is made in eliminating gender inequalities in land ownership.